The Prevalence of Iron Deficiency Anemia among Pregnant Women in Ibn- Albaldy Hospital - Gatea, abeer; Tawfeeq, wafaa; hassan, Muna (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: To study the prevalence of iron deficiency anemia in pregnant women and to find out the degree of iron deficiency anemia and to find out any association this has been found between the socio- demographic characteristics and the degree of iron deficiency anemia. Methodology: A cross sectional study has been conducted in Ibn-Albaldy hospital in Baghdad among 258 pregnant women attending outpatient clinics during the period from the 1st of March 2011 to fifteenth of October 2011. Data collection was by using a previously designed questionnaire including socio-demographic characteristics, obstetrical history. A blood sample has been obtained to estimate the hemoglobin, mean corpuscular volume, serum iron and iron binding capacity. Results: The most frequent age group was 20-29 years 101(39.2%). Moderate degree anemia found in 100(38.8%), severe anemia in 55(21.3%), mean hemoglobin was 9.2 ±3.5 SD, mean corpuscular volume 109 ±26.1 SD, mean serum feritin 48.7 ± 46.6 SD, mean serum iron 104 ±62SD and total iron binding capacity 458 ± 91. Significant association has been found between degree of anemia and age and educational level. Recommendation: Interventions to enhance the intake of diet rich in iron and the intake of iron supplements for all pregnant women.